Cloning and bioinformatic analysis of drought-related genes in soybean (Glycine Max L.) - Khatamov Dilmurod; Kadirova Zukhra; Usmanov Abdijabbar; Nazarov Kholmurzo; Aberkulov Mardan (BIO Web of Conferences)
This study investigates the GmSOG1 gene in soybean (Glycine max L.) and its role in drought tolerance. Through bioinformatic analysis, GmSOG1 was identified as a key stress-responsive gene. The CRISPR/Cas9 genome-editing technique was used to target and modify this gene, resulting in the development of mutant lines. Functional analysis showed that GmSOG1 positively regulates antioxidant enzyme activity and the expression of drought-responsive transcription factors, thereby improving plant survival under water deficit conditions. The successful transformation of local soybean cultivars using Agrobacterium tumefaciens and CRISPR/Cas9 confirmed the gene’s relevance in enhancing drought resistance. This research provides a solid foundation for developing resilient soybean varieties and contributes to sustainable agriculture amid climate change challenges.